2011
DOI: 10.1002/dev.20525
|View full text |Cite
|
Sign up to set email alerts
|

Neural signatures of face–voice synchrony in 5‐month‐old human infants

Abstract: Infants' unitary perception of their multisensory world, including learning from people (faces and speech), hinges on temporal synchrony. Despite its importance, relatively little work has investigated the brain processes involved in infants' perception of temporal synchrony. In two experiments, we examined event-related brain potentials (ERPs) to asynchronous and synchronous audio-visual speech in infants. Both experiments showed the early auditory P2 was greater for the synchronously presented pairings and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
62
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(77 citation statements)
references
References 65 publications
11
62
4
Order By: Relevance
“…In 5-month olds, they observed differential attentional responses (Nc), with a greater response to faces paired with congruent emotional voices compared to faces paired with incongruent emotional voices regardless of the race of the face (African American or Caucasian). Like findings reported on above, the direction of these results is consistent with some previous work (Reynolds et al, 2014) and opposite of what others have found (Knopp, 2014;Grossmann et al, 2006;Hyde et al, 2011). In contrast, 9-month olds did not show attentional response (Nc) differences by congruency in emotion between faces and voices.…”
Section: ----------------------------Insert Figure 3 About Here -----supporting
confidence: 88%
See 4 more Smart Citations
“…In 5-month olds, they observed differential attentional responses (Nc), with a greater response to faces paired with congruent emotional voices compared to faces paired with incongruent emotional voices regardless of the race of the face (African American or Caucasian). Like findings reported on above, the direction of these results is consistent with some previous work (Reynolds et al, 2014) and opposite of what others have found (Knopp, 2014;Grossmann et al, 2006;Hyde et al, 2011). In contrast, 9-month olds did not show attentional response (Nc) differences by congruency in emotion between faces and voices.…”
Section: ----------------------------Insert Figure 3 About Here -----supporting
confidence: 88%
“…There is some evidence that the neural response of infants is greater to bimodal compared to unimodal stimulation, paralleling that observed in adults and non-human animals (e.g., Besle et al, 2004;Giard & Peronnet, 1999;Pilling, 2009;Reynolds et al, 2014;Brefczynski-Lewis et al, 2009;Wallace & Stein, 1997;Wallace, Wilkinson, & Stein 1996). Infants also appear to integrate information from different senses early during sensory processing in some contexts, as has also been documented routinely in adults (Hyde et al, 2011;Besle et al, 2009). Further, later attentional responses in adults and infants distinguish between bimodal audio-visual stimulation containing redundant (e.g., synchronous) and non-redundant (e.g., asynchronous) visual face and auditory voice information (Hyde et al, 2011, Grossmann et Intersensory Perception 26 al., 2006Reynolds et al, 2014;Vogel et al, 2012;Besle et al, 2009).…”
Section: ----------------------------Insert Figure 3 About Here -----supporting
confidence: 60%
See 3 more Smart Citations